Pemetaan Etnobotani Secara Partisipatif pada Suku Orang Rimba Kecamatan Bangko Kabupaten Merangin Jambi - Widiyantoro, Bagas; Nirwansyah, Anang Widhi; Wuliandari, Juli Rochmijati; Suwarno, Suwarno (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
The Suku Orang Rimba (SOR) is one of the indigenous people who still uphold ancestral traditions utilizing local knowledge to conserve forest resources. This includes maintaining forest resources that can be used as a buffer for the interests and needs of indigenous peoples both for consumption, economic, and religious ritual needs. However, territorial conflicts and unilateral claims by interested parties often damage SOR's living space and take advantage of forest areas as land for industry. The local indigenous knowledge of the SOR that is not recognized and without clear evidence also causes the rights to the land where SOR lives and livelihoods are also threatened. This study aims to conduct ethnobotanical mapping of SOR in a participatory manner by utilizing the local knowledge of indigenous peoples and providing opportunities so that SOR in Taman Nasional Bukit Duabelas (TNBD) can learn independently in making and owning their maps. Participatory mapping in this study is divided into five stages, namely the training stage, survey study, data processing and modeling, descriptive study, and evaluation study. The research instruments in this study are earth-like maps, mapping survey tools in the form of GPS, and GIS software. The results of this study are a map of ethnobotanical distribution in SOR, consisting of 64 ethnobotanical points categorized into seven categories of mapping objects with supporting information from interview results, and literature studies that have been carried out. From this participatory ethnobotanical mapping activity, it shows that the SOR mapping team in addition to playing an active role in communicating clearly and transparently about the object of study under study also contributes directly to determining the direction of surveying and mapping, can encourage active public awareness increase, and has the capacity and capability to master survey and mapping practices so that maps and map making can be tools and/or part of the community as proof of the right to life of the SOR indigenous people in TNBD.Keywords: Suku Orang Rimba, participatory mapping, ethnobotany, TNBD